186k views
3 votes
50 points.

Please simplify.
Please answer it correctly and don't answer of you don't know otherwise I'll report it to higher authorities.​

50 points. Please simplify. Please answer it correctly and don't answer of you don-example-1
User Maalamaal
by
5.4k points

2 Answers

2 votes

well you already got an answer so can i have free 25

User MintyAnt
by
5.1k points
5 votes

Answer:

1

Explanation:

Using the rules of exponents


(a^m)^(n) =
a^(mn)


a^(m) ×
a^(n) =
a^((m+n))

Given


((1)/(x^((a-b))) ) ^(a+b) ×
((1)/(x^(b+a)) ) ^(b-a)

=
(1)/(x^((a-b)(a+b)) ) ×
(1)/(x^((b+a)(b-a)) )

=
(1)/(x^((a^2-b^2)) ) ×
(1)/(x^((b^2-a^2)) )

=
(1)/(x^((a^2-b^2+b^2-a^2)) )

=
(1)/(x^(0) )

=
(1)/(1)

= 1

User Dfritsi
by
5.3k points